Sustainable Supply Chains in Industrial Engineering and Management (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
The integration of information technologies with industry has marked the beginning of the fourth industrial revolution and promoted the development of industrial engineering. However, the depletion of resources and industrial waste caused by increasing amounts of industrial production pose a huge threat to nature. The application of sustainable supply chains in industrial engineering and management is one of the ways to balance the economy, society and environment. Therefore, it is a key concern for us to explore the construction of sustainable supply chains in industrial engineering and management. Moreover, to understand the impact of low-carbon, sustainable and recycled supply chains on industrial engineering, we need more in-depth investigations.This Special Issue aims to solicit original research and review articles discussing sustainable supply chain decision-making in industrial engineering and management to improve the sustainability of enterprise operations. Moreover, this Special Issue also shows mixed methods (e.g., modeling plus a case study) and rigorous quantitative/qualitative empirical studies of sustainable supply chains.